2012
DOI: 10.1007/s10637-012-9871-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel proteasome inhibitor acting in mitochondrial dysfunction, ER stress and ROS production

Abstract: Summary In cancer-treatment, potentially therapeutic drugs trigger their effects through apoptotic mechanisms. Generally, cell response is manifested by Bcl-2 family protein regulation, the impairment of mitochondrial functions, and ROS production. Notwithstanding, several drugs operate through proteasome inhibition, which, by inducing the accumulation and aggregation of misfolded or unfolded proteins, can lead to endoplasmic reticulum (ER) stress. Accordingly, it was shown that Amblyomin-X, a Kunitz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 57 publications
4
36
0
1
Order By: Relevance
“…The prolongation of PT and aPTT is reversible [154]. Interestingly, several studies pointed out Amblyomin-X as an anti-cancer molecule in vitro and in vivo [154][155][156][157][158][159][160][161].…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
“…The prolongation of PT and aPTT is reversible [154]. Interestingly, several studies pointed out Amblyomin-X as an anti-cancer molecule in vitro and in vivo [154][155][156][157][158][159][160][161].…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
“…Furthermore, we found that the level of proteasome inhibition in HOS cells was higher than in HT1080 cells. Previous studies have demonstrated that proteasome inhibition induces cell death through ER stress [25,26]. Therefore, to detect the expression of the ER stress-related protein IRE1α, we performed western blotting with lysates from cells receiving each of the different concentrations of ATO (Fig.…”
Section: Cytotoxicity Er Stress and Proteasome Activity In Osteosarcmentioning
confidence: 99%
“…The data accumulated thus far have revealed that ER stress leads to autophagy through the ER stress-induced inhibition of mTOR or direct activation of Atg pro-autophagic genes [26]. Therefore, we investigated whether inhibition of ER stress could change the percentage of apoptotic and autophagic cells that had been treated with ATO.…”
Section: Er Stress Inhibition Suppresses Ato-induced Apoptosis Autopmentioning
confidence: 99%
“…Bax and the adenine nucleotide translocator cooperate within the permeability transition pore complex, increasing mitochondrial membrane permeability. This increase in permeability results in the release of cytochrome c, apoptosis-inducing factor, and other pro-apoptotic molecules from the mitochondria into the cytoplasm, and consequently, these proteins can promote the activation of executioner caspases (3, 6 and 7), leading to apoptosis [15,43,47].…”
Section: Discussionmentioning
confidence: 99%